PSYCHOLOGICAL CHARACTERISTICS AND QUALITY OF LIFE OF PARENTS OF CHILDREN WITH DISABILITIES - Senad Mehmedinović; Vesna Bratovčić; Edina Šarić; Alma Huremović; Alma Mehmedinović; Benjamin Avdić (Research in Education and Rehabilitation, 2025)
The aim of this research was to determine differences in the levels of anxiety, depression, perceived stress, and quality of life among parents of children with different developmental difficulties (intellectual disabilities, autism spectrum disorder, and cerebral palsy). The sample consisted of 104 parents, the majority of whom were female (85.6%). Most parents reported that their child had an autism spectrum disorder (45.2%), while the rest reported Down syndrome (29.8%) and cerebral palsy (25.0%). The following instruments were used for the purposes of the research: Demographic Data Questionnaire, Perceived Stress Scale (PSS), Family Quality of Life Scale (FQoL), Generalized Anxiety Disorder Scale (GAD-7), and the Patient Health Questionnaire (PHQ-9). Statistical data analysis was conducted using univariate analysis of variance (ANOVA). The results showed that parents of children with cerebral palsy exhibit statistically significantly higher levels of anxiety, depression, and perceived stress compared to parents of children with autism and Down syndrome. These findings confirm previous research on the impact of the complexity of motor impairments on the psychological state of parents and highlight the need for targeted psychosocial support for this population. On the other hand, the study did not show statistically significant differences in the perception of overall quality of life among parents, regardless of the type of their child's difficulty. This result implies that factors such as family support, adopted coping mechanisms, and the degree of acceptance of the situation may play a key role in maintaining the subjective sense of life homeostasis.